PRODUÇÃO DE MUDAS DE BARBATIMÃO (STRYPHNODENDRON ADSTRINGENS) CULTIVADAS EM SUBSTRATO A BASE DE LODO DE ESGOTO - Mazzini, Geovani; Nobrega, Michele; Pontes, Montcharles; Sefara, Shaline; Santiago, Etenaldo (ANAIS DO ENIC, 2018)
-